LA ENTREVISTA EN LA INVESTIGACIÓN CUALITATIVA: NUEVAS TENDENCIAS Y RETOS. THE INTERVIEW IN THE QUALITATIVE RESEARCH: TRENDS AND CHALLENGERS - Vargas-Jiménez, Ileana (UNIVERSIDAD ESTATAL A DISTANCIA, 2012)
En el siguiente artículo se analiza la entrevista dentro de la investigación cualitativa. Para ello, se aborda el origen de la entrevista, así mismo, se explican tres tipos de entrevista (estructurada, no estructurada y de grupos), se analizan las nuevas tendencias y los retos en el uso de la entrevista, y se finaliza con las conclusiones del artículo.Palabras clave: Entrevista, investigación cualitativa, entrevista estructurada, entrevista no estructurada, entrevista grupal, nuevas tendencia de entrevista, conclusiones.AbstractThis article is intended to provide an insight as what it is the interview, when carrying out a qualitative research, throughout this article, the origin of the basis interview is defined. After it, there are three kinds of different interviews: the structured interview, non structured and the groups, subsequently, new tendency of the use of interview, finally some final thoughts on this matter are given.Keywords: Interview, qualitative research, structured interview, no structured interview, interview groups, new trends and challengers in interview and the conclusions.